Implementation of a new separation method to produce qualitatively improved 64Cu. (11th July 2019) - van der Meulen, Nicholas P.; Hasler, Roger; Blanc, Alain; Farkas, Renata; Benešová, Martina; Talip, Zeynep; Müller, Cristina; Schibli, Roger
Abstract : Background: 64 Cu ( T 1/2  = 12.7 h) is an important radionuclide for diagnostic purposes and used for positron emission tomography (PET). A previous method utilized at Paul Scherrer Institute (PSI) proved to be unreliable and, while a method using anion exchange chromatography is a popular choice worldwide, it was felt a different approach was required to obtain a robust chemical separation method. Methods: Enriched 64 Ni targets were created by electroplating on gold foil. The targets were irradiated with protons degraded to approximately 11 MeV at PSI's Injector 2 72 MeV research cyclotron and subsequently dissolved in HCl. The resultant solution was loaded onto AG MP‐50 cation exchange resin and the 64 Cu separated from its target material and radiocobalt impurities, produced as part of the irradiation process, using various specific mixtures of HCl/acetone solution. The eluted product was evaporated and picked up in dilute HCl (0.05 M). The chemical purity of 64 Cu was determined by radiolabeling experiments at the highest possible molar activities. Results: Reproducible results were obtained, yielding 3.6 to 8.3 GBq 64 Cu of high radionuclidic and radiochemical purity. The product was labeled to NODAGA‐RGD, achieved at up to 500 MBq/nmol, indicating the high chemical purity. In a proof‐of‐concept in vivo study, 64 Cu‐NODAGA‐RGD was used for PET imaging of a tumor‐bearing mouse. Conclusion: The chemical separation devised to produce high‐quality 64 Cu proved to be robust and reproducible. The concept can be used at medical cyclotrons utilizing a solid target station, such that 64 Cu can be used at hospitals for PET imaging. Abstract : A new robust and reproducible chemical separation method was devised to produce high‐quality 64 Cu from enriched 64 Ni target material, utilizing a macroporous cation exchange resin and various concentrations of HCl‐acetone media. The quality of the final product was of high radionuclidic and chemical purity. The concept can be applied at facilities with medical cyclotrons installed with a solid target station, such that 64 Cu can be utilized for PET imaging.